Feasibility pilot study of a Japanese teaching kitchen program - Baden, Megu Y.; Kato, Sarasa; Niki, Akiko; Hara, Tomoyuki; Ozawa, Harutoshi; Ishibashi, Chisaki; Hosokawa, Yoshiya; Fujita, Yukari; Fujishima, Yuya; Nishizawa, Hitoshi; Kozawa, Junji; Muraki, Isao; et al. (Frontiers in Public Health, 2023)
Background This pilot study examined the feasibility of a new lifestyle modification program involving a “Teaching Kitchen” in Japan. Our goal was to explore (1) feasibility of the program; (2) acceptability for class frequency (weekly vs. bi-weekly); and (3) changes in biometrics, dietary intakes, and lifestyle factors. Methods A total of 24 employees with obesity in a Japanese company were recruited. Participants were randomly divided into two groups (weekly or bi-weekly group), each attending the program consisting of four two-hour classes (lectures on nutrition, exercise, mindfulness, and culinary instructions). Participants were observed for changes in dietary intakes, biometrics, and health related quality of life over the subsequent 3 months. We tested the between-group differences in changes using linear mixed-effect models. Results The program completion rates were 83.3% in total (91.7% for weekly group and 75.0% for bi-weekly group). From baseline to post-intervention, significant decreases were observed in weight (p < 0.001), body mass index (p < 0.001), diastolic blood pressure (p = 0.03), body fat mass (p < 0.001), and dietary intakes in total fat (p = 0.03) and sodium (p = 0.008) among 17 participants who were available for measurements. Improvements in biometrics remained significant 1 month after the intervention (all p ≤ 0.03 in 14 participants). Participants' health related quality of life was significantly improved in bodily pain, general health, vitality, and mental component score (all p ≤ 0.047). Conclusions The new Japanese Teaching Kitchen program is feasible with high program completion rates in Japanese office workers with obesity. While this was a small feasibility study, significant multiple improvements in dietary intakes, biometrics, and health related quality of life suggest that this line of inquiry warrants further exploration to address obesity and obesity-related diseases in Japan.